KITCHEN ISLAND FURNITURE DESIGN FOR RESIDENTIAL HOUSES - Patricia Isabela Braileanu (Journal of Industrial Design and Engineering Graphics, 2017)
In terms of spatial configuration, kitchen and their arrangement in the assembly, storage and distribution areas place. This paper focuses upon designing a prototype by taking into account the kitchen geometry as different materials and their properties, th ensure a long lifespan of the product at a minimum cost.